Asupan Gizi Dan Pola Makan Pada Anak Yang Berstatus Gizi Baik Dan Kurang Gizi Sebagai Informasi Untuk Perbaikan Gizi Siswa SD: Holil M. Par'i*) dan RR Nur Fauziyah*) - Poltekkes Kemenkes Bandung (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2008)
Under nutrition problem among elementary school children is a serious obstacle on the effort of human resources development through education. Therefore, raising nutrition status on school children must have serious attention. Nutritional status is influenced by two main factors that are food intake and illness. Inapproriate food habit has impact on under nutrition condition. The aim of the study is to analyze the relationship between nutrient intake, eating pattern and nutritional status. The research design is cross sectional. The research was carried out on July 2003 at Elementary Schoolchildren grade I, II and III in District Cimahi West Java. The samples consist of 104 students. The Result of the study indicates that there was 30.8% students under nutrition based on weight by age indicator and there was 29,8 % student children. The mean of caloric intake was 1225 caloric per day and 32.9 gram protein per day. This number is still under the recommended daily allowance (RDA) for Indonesian. The result of statistic test shows that there was a significant relationship between caloric and protein intake and the nutritional status among school children (P<0.05).